Effect of barley in starter diets for swine - Robert D Goodband; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1985)
Two-hundred and forty weanling pigs averaging 14.0 Ibs. were utilized in two growth trials to evaluate the effects of increasing levels of barley in the diet. Milo was replaced by barley pound for pound at levels of 10, 20, 30, and 40% of the diet. Neither average daily gain, feed intake, nor feed efficiency were affected by the increasing levels of barley. These results indicate that barley may replace all of the milo in a 20%-whey nursery diet.; Swine Day, Manhattan, KS, November 21, 1985
Keywords: Swine day; 1985; Kansas Agricultural Experiment Station contribution; no. 86-145-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 486; Swine; Barley; Starter diets